Measuring efficiency of working capital management: a two-stage data envelopment analysis approach. (2016) - Goel, Utkarsh; Sharma, Anil K.
The purpose of this paper is to analyse the efficiency of working capital management (WCM) in Indian manufacturing firms during the period 2004-2013. The paper describes and uses a new approach based on data envelopment analysis (DEA) to measure the WCM efficiency of firms. Two-stage bootstrapped DEA is employed to first calculate the efficiency and then analyse the effect of exogenous variables on it. We find that the average WCM efficiency over the last ten years was around 40% and majority of the firms were on the lower side of the average. Firm-specific factors like firm's age, proportion of fixed assets, return on asset and sales growth are found to have significant effect on efficiency, whereas macroeconomic factors have a somewhat inconsistent effect. The paper further suggests that the DEA-based measure is not only able to overcome the limitations of traditional measures like mathematical incorrectness and assignment of fixed weights to constituents but also offers several additional advantages.